ความสัมพันธ์ระหว่างความรู้สึกไม่แน่นอนในความเจ็บป่วย แรงสนับสนุนทางสังคมกับการปรับตัวของผู้สูงอายุโรคข้อเข่าเสื่อม - สุณี สุวรรณพสุ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The purposes of this research were to study the relationships between uncertainty in illness, social support and adaptation. Subjects were 150 elderly with osteoarthritis at King Chulalongkorn Memorial Hospital selected by simple random sampling technique. Data were collected using instruments: uncertainty in illness scale, social support questionnaires, and adaptation questionnaire. The questionnaires were tested for content validity by panel of experts. Alpha Cronbach coefficients were .85, .94, and .91, respectively. The data were analyzed using Pearson s product moment correlation and stepwise multiple regression at the significant level of .05. The major findings were as follows: 1. The adaptation of elderly with osteoarthritis was at a moderate level. (X =2.81) 2. The social support of elderly with osteoarthritis was at a moderate level. (X = 2.15) 3. The uncertainty in illness of elderly with osteoarthritis was at a moderate level. (X = 2.37) 4. The relationship between uncertainty in illness and adaptation was negatively significant (r =-.498 ,p<.05). 5. The relationship between social support and adaptation was positively significant (r=.685 ,p<.05). 6. Uncertainty in illness and social support were the variables that significantly predicted adaptation at the level of .05. These predictive power was at 52.2 % (R2) of the variance. Adaptation of elderly with osteoarthritis = .578 social support - .253 uncertainty in illness.